2004
DOI: 10.1158/1078-0432.ccr-03-0589
|View full text |Cite
|
Sign up to set email alerts
|

EphA2 Expression Is Associated with Aggressive Features in Ovarian Carcinoma

Abstract: Purpose: EphA2 (epithelial cell kinase) is a transmembrane receptor tyrosine kinase that has been implicated in oncogenesis. There are no published data regarding the role of EphA2 in ovarian carcinoma, which is the focus of the present study.Experimental Design: Nontransformed (HIO-180) and ovarian cancer (EG, 222, SKOV3, and A2780-PAR) cell lines were evaluated for EphA2 by Western blot analysis. Five benign ovarian masses, 10 ovarian tumors of low malignant potential, and 79 invasive ovarian carcinomas were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
174
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 194 publications
(185 citation statements)
references
References 44 publications
10
174
1
Order By: Relevance
“…EphA2 overexpression has been reported to correlate with aggressive features in other human tumor types [10][11][12][13][14][15][16][17][18][19]. Consistent with these reports, we found a significant increase in EphA2 expression in pancreatic cancers as compared to benign ducts and PanIN lesions, as well as increased expression in poorly differentiated carcinomas compared to well or moderate differentiated carcinomas (P < 0.005).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…EphA2 overexpression has been reported to correlate with aggressive features in other human tumor types [10][11][12][13][14][15][16][17][18][19]. Consistent with these reports, we found a significant increase in EphA2 expression in pancreatic cancers as compared to benign ducts and PanIN lesions, as well as increased expression in poorly differentiated carcinomas compared to well or moderate differentiated carcinomas (P < 0.005).…”
Section: Discussionsupporting
confidence: 90%
“…Instead, ephrinA binding seems to regulate EphA2 subcellular localization and interaction with other downstream signaling proteins including FAK and the MAP/ERK signaling pathways [8,9]. EphA2 is overexpressed in a variety of human cancers, and high levels of EphA2 are associated with aggressive disease and poor clinical outcomes [10][11][12][13][14][15][16][17][18][19]. In vitro studies have shown that EphA2 is a powerful oncoprotein, sufficient to confer malignant potential on non-transformed epithelial cells [7].…”
Section: Introductionmentioning
confidence: 99%
“…The percentage of positive tumor cells was defined using the following scores: 0=0-5%, 1=6-25%, 2=26-50%, 3=51-75%, 4=76-100%. The final immunoreactive score was determined by the sum of both points: 0-1: negative expression (-), 2-3: weak expression (+), 4-5: moderate expression (++), 6-7: strong expression (+++) (Thaker et al, 2004;Ito et al, 2006).…”
Section: Immunohistochemistry and Immunocytochemistrymentioning
confidence: 99%
“…[14][15][16] We have previously demonstrated that EphA2 is overexpressed in 76% of epithelial ovarian cancers. 17 This increased expression was associated with high tumor grade and stage as well as decreased overall survival. 17 We have also demonstrated that increased EphA2 expression in ovarian cancer samples is strongly associated with critical factors involved in angiogenesis and invasion such as greater microvessel density and higher matrix metalloproteinase (MMP) expression.…”
Section: Introductionmentioning
confidence: 97%
“…17 This increased expression was associated with high tumor grade and stage as well as decreased overall survival. 17 We have also demonstrated that increased EphA2 expression in ovarian cancer samples is strongly associated with critical factors involved in angiogenesis and invasion such as greater microvessel density and higher matrix metalloproteinase (MMP) expression. 18 Based on the high frequency of EphA2 overexpression and its association with aggressive tumor features, we and others have employed either agonist antibodies or in vivo siRNA to decrease EphA2 levels.…”
Section: Introductionmentioning
confidence: 97%